Influence of coating-blanching in starch solutions, on the drying kinetics, transport properties, quality parameters, and microstructure of celery root chips - Kian-Pour, Nasim; Akdeniz, Esra; Toker, Omer Said (ELSEVIER, 2022)
The possibility of using different types of starches as the drying aid materials before hot air drying (HAD) (110 degrees C, 1.5 m/s) of celery root chips to improve drying kinetics and the quality of products were investigated. The influence of coating-blanching pre-treatment of the samples in the native and modified corn, tapioca, and wheat starch solutions (0.1%, 0.3%, 0.5% (w/w)) on the drying kinetics, transport properties, microstructure, color, and texture of the samples was studied. The effective diffusion coefficients varied from 0.735 x 10(-9) m(2)/s to 2.396 x 10(-9) m(2)/s. The drag force, heat, and mass transfer coefficients were determined as 8.327 x 10-6 N, 41.21 W/m(2)K, and 0.0341 m/s, respectively. In terms of mathematical modeling, the Midilli & Kucuk model was the best for describing the drying behavior of the samples. The fracturability of all samples increased after coating-blanching and the highest L* value and the maximum compact microstructure were observed in the native and modified corn starch samples. Coating-blanching in the native and modified corn starch solutions was a promising alternative technique to reduce drying time and improve drying kinetics, texture, and color of celery root chips.
Keywords: Celery root chips; Coating-blanching pre-treatment; Corn starch; Microstructure; Drying kinetics; PHYSICOCHEMICAL PROPERTIES; FUNCTIONAL-PROPERTIES; HEAT-TREATMENT; HOT AIR; APPLE; TEMPERATURE; TEXTURE; Food Science & Technology